Relationships Among Independent Major Depressions, Alcohol Use, and Other Substance Use and Related Problems Over 30 Years in 397 Families - Schuckit, Marc A. (Rutgers University, 2013)
OBJECTIVE: Although heavy drinking is related to sadness on multiple levels, the link between alcohol use disorders (AUDs) and major depressive episodes (MDEs) is more controversial. One complicating factor is that some MDEs are temporary and only occur in the context of heavy drinking, whereas other MDEs are longer lasting and occur independently of intense alcohol intake (i.e., independent depressive episodes [IDEs]). We hypothesized that a longitudinal study that uses validated interviews with subjects and relatives and distinguishes between IDEs and alcohol-induced depressive episodes would reveal little evidence of a link between IDEs and AUDs. METHOD: Histories of AUDs, IDEs, and substance-induced depressions were prospectively evaluated over 30 years in 397 male probands from the San Diego Prospective Study and in their 449 offspring using questions extracted from the Semi-Structured Assessment for the Genetics of Alcoholism interview. RESULTS: The rate of IDEs over 30 years in the 397 probands was 15.3% overall. Among probands who developed AUDs, 31% of their depressive episodes were substance induced, not IDEs. For these men followed over 3 decades, those with IDEs had no increased rate of AUDs and evidenced no higher rate of use or abuse/dependence on illicit substances. Similar conclusions applied to their 449 offspring ages 12 years and older. CONCLUSIONS: These data support the importance of distinguishing between IDE and substance-induced depressions when evaluating the relationship between AUDs and depression syndromes.